To reflect a triangle across the y-axis, we need to change the x-coordinates of each vertex to their opposite (negative) values while keeping the y-coordinates the same.
Given the coordinates of triangle \( A'B'C' \):
- \( A' = (5, -1) \)
- \( B' = (5, -9) \)
- \( C' = (2, -7) \)
Now, reflecting each point across the y-axis:
-
For point \( A' = (5, -1) \):
- New coordinates: \( A" = (-5, -1) \)
-
For point \( B' = (5, -9) \):
- New coordinates: \( B" = (-5, -9) \)
-
For point \( C' = (2, -7) \):
- New coordinates: \( C" = (-2, -7) \)
Thus, the new coordinates after reflecting triangle \( A'B'C' \) across the y-axis to create triangle \( A"B"C" \) are:
- \( A" = (-5, -1) \)
- \( B" = (-5, -9) \)
- \( C" = (-2, -7) \)